Patterson v. McLean: A Confirmation of the New Right at the U.S. Supreme Court - Sullivan, George (Les Cahiers de droit, 1989)
In two consecutive national elections a conservative, Ronald Reagan, was elected President of the United States. When Justice Lewis Powell announced his retirement during the late months of the Reagan administration, it was apparent that the President's last appointment could shift the ideology of the Court to conservatism for the first time since the presidency of Dwight Eisenhower. President Reagan's prior appointments, Sandra Day O'Connor and Antonin Scalia, had joined William Rehnquist, an appointee of President Nixon and Bryon White, an appointee of President Kennedy to comprise a vociferous minority of four in many instances, especially cases involving civil rights. The unexpected opportunity for the appointment of a conservative jurist caused great anxiety in the media and in the U.S. Senate, the later having confirmation power over presidential appointments to the Supreme Court. This article examines the consequences of the Senate's confirmation of Justice Anthony Kennedy to the Supreme Court. The impact, which was immediate and dramatic, indicates that conservative ideology will predominate on major civil rights issues for the remainder of this century.